Impact of Service Station Networks on Purchase Decisions of Alternative-fuel Vehicles - Martin Achtnicht; Georg Bühler; Claudia Hermeling (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
In this paper we analyze the impact of service station availability on the demand for alternative-fuel vehicles and the consumers' willingness to pay for an enlarged fueling infrastructure. We examine a stated preferences choice experiment conducted as a CAPI survey with about 600 interviews of potential car buyers in Germany and estimate the coefficients of a discrete choice model. We simulate different scenarios and analyze how individual choice probabilities for alternative fuel-types are changing with a modified fueling infrastructure. In our scenarios hybrids, LPG/CNG and hydrogen will be real alternatives to the existing conventional technologies. However, biofuels and electric power trains are well behind even in a situation where their infrastructure is equally developed. Moreover, on the basis of our model we compute what increases in fixed or variable costs consumers of different income groups are willing to accept for an increasing station density.
Keywords: R41; L62; C51; 330; Fueling Infrastructure; Alternative Fuels; Automobile Market; Stated Preferences; Discrete Choice; Network Effects; Kraftstoff; Regenerative Energie; Tankstelle; Infrastruktur; Konsumentenverhalten; Kraftfahrzeug; Umweltverträgliches Produkt; Deutschland